High-safety and high-energy-density positive pole piece structure

By designing a carbon primer layer, an active material layer and a lithium-rich lithium-enriched lithium-enhancing layer in the positive electrode sheet structure, combined with a solid electrolyte layer, the problem of difficult to take into account both the energy density and safety of the positive electrode material in the prior art is solved, and a battery positive electrode sheet structure with high energy density and high safety is achieved.

CN222600988UActive Publication Date: 2025-03-11TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202323520772.1
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2023-12-22
Publication Date
2025-03-11
Estimated Expiration
2033-12-22

AI Technical Summary

Technical Problem

In the prior art, on the basis of meeting the high safety of the cathode material, it is still difficult to improve the energy density.

Method used

A high-safe and high-energy density positive electrode sheet structure is designed, including a carbon primer layer, a first active material layer, a lithium-rich lithium-energy layer, a second active material layer and a solid electrolyte layer. Through the combination and structural optimization of these layers, the energy density and safety of the positive electrode material are improved.

Benefits of technology

While increasing the energy density of the positive electrode material, the safety of the battery is significantly improved, the binding force between the current collector and the positive electrode active material is enhanced, the corrosion of the electrolyte on the current collector is reduced, and the stability and circulation performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222600988U_ABST
    Figure CN222600988U_ABST
Patent Text Reader

Abstract

The utility model provides a high-safety and high-energy-density positive pole piece structure which sequentially comprises a carbon bottom coating, a first active material layer, a lithium-rich lithium supplementing layer, a second active material layer and a solid electrolyte layer from at least one side of a current collector to the outside. Through the structural sequence design of the positive pole pieces, the energy density of the positive pole material is improved, and the safety of the battery is improved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of battery structure design, in particular to a positive electrode plate structure with high safety and high energy density. Background Art

[0002] Positive electrode materials are an important component of lithium batteries. During the battery charging and discharging process, positive electrode materials not only serve as a lithium source, but also bear the lithium consumed by the formation of SEI film on the surface of the negative electrode material of the battery. The structural morphology of the positive electrode material will also affect the lithium required for the reciprocating insertion and removal of lithium between the positive and negative electrodes of the battery. Therefore, the ideal positive electrode material must have the following characteristics: high specific capacity, high energy density, good safety, good rate performance and long life.

[0003] At present, the materials that can meet the above requirements are mainly divided into three types according to their structural characteristics: lithium cobalt oxide, lithium nickel oxide, and nickel cobalt manganese oxide with layered structures; lithium manganese oxide materials with spinel structures; lithium iron phosphate and lithium iron manganese phosphate materials with olivine structures. Layered structured positive electrode materials are very suitable for the insertion and extraction of lithium ions, and have the advantages of high energy density and high specific capacity, but poor thermal stability. Spinel structured positive electrode materials have high thermal stability, low cost, and good safety, but low energy density. Olivine structured positive electrode materials have low cost, good stability, and long life, but low energy density and poor conductivity. It is still difficult for existing technologies to improve energy density while meeting the high safety of positive electrode materials. Summary of the invention

[0004] In order to solve the above problems, the utility model provides a high-safety and high-energy-density positive electrode plate structure, which can improve the energy density of the positive electrode material while enhancing the safety of the battery.

[0005] The utility model provides a high-safety and high-energy-density positive electrode plate structure, which includes a carbon base coating, a first active material layer, a lithium-rich lithium-supplementing layer, a second active material layer, and a solid electrolyte layer in sequence from at least one side of a current collector to the outside.

[0006] In some embodiments, the current collector is selected from one of an aluminum foil current collector, a titanium foil current collector, and a silver foil current collector.

[0007] In some embodiments, the carbon base coating material is selected from one of graphene, nano carbon black, acetylene black, graphite, carbon nanotubes, and carbon nanowires. The aluminum foil current collector with the carbon base coating can also be directly purchased as an integrated product.

[0008] In some embodiments, the carbon primer layer has a thickness of 0.1-1 μm. Preferably, the carbon primer layer of the present application has a thickness of 500-600 nm.

[0009] In some embodiments, the first active material layer is selected from a layered structure positive electrode material, and the second active layer material is selected from a spinel structure positive electrode material or an olivine structure positive electrode material.

[0010] In some embodiments, the layered positive electrode material is selected from at least one of NCM811, NCM622, NCM523, lithium cobalt oxide, and lithium nickel oxide. Preferably, the layered positive electrode material is selected from one of NCM811, NCM622, and NCM523.

[0011] In some embodiments, the spinel structure positive electrode material is selected from lithium manganese oxide, and the olivine structure positive electrode material is selected from at least one of lithium iron phosphate and lithium iron manganese phosphate.

[0012] In some embodiments, the lithium-rich lithium-supplementing layer material is selected from one of lithium salts or metallic lithium. The lithium salt is selected from one of lithium manganate, lithium nickelate, lithium vanadate, lithium titanate, and lithium oxalate. Preferably, the lithium-rich lithium-supplementing layer material of the present application is selected from lithium oxalate.

[0013] In some embodiments, the thickness of the first active material layer is 100-600 μm. Preferably, the thickness of the first active material layer of the present application is 100-300 nm. The thickness of the second active material layer is 50-300 μm. Preferably, the thickness of the second active material layer of the present application is 70-100 nm. The ratio of the thickness of the second active material layer to the thickness of the first active material layer is ≤0.5.

[0014] In some embodiments, the lithium-rich lithium-supplementing layer has a thickness of 1-50 μm. Preferably, the lithium-rich lithium-supplementing layer has a thickness of 5-10 μm.

[0015] In some embodiments, the solid electrolyte layer material is selected from one of a polymer electrolyte, an oxide electrolyte, and a sulfide electrolyte. The polymer electrolyte is selected from at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), and polyvinylidene fluoride (PVDF). The oxide electrolyte is selected from at least one of lithium phosphorus oxynitride (LiPON), lithium aluminum titanium phosphate (LATP), lithium lanthanum titanium oxide (LLTO), and lithium lanthanum zirconium oxide (LLZO). The sulfide electrolyte can be selected from lithium thiophosphate (Li3PS4), high purity germanium sulfide germanium disulfide (Li 10 GeP2S 12 ), lithium thiophosphate (Li7P3S 11 Preferably, the solid electrolyte of the present application is selected from polymer electrolytes.

[0016] In some embodiments, the first active material layer has a porosity of 35-50%, the second active material layer has a porosity of 35-50%, and the solid electrolyte layer has a porosity of ≥50% and a thickness of 0.5-10 μm.

[0017] The beneficial effects of the utility model are:

[0018] A carbon base coating is designed on the current collector to enhance the bonding force between the current collector and the positive electrode active material, while avoiding the erosion of the electrolyte on the current collector and improving the stability of the battery. The material of the first active material layer is selected from a layered positive electrode material with high energy density but slightly low thermal stability, and the material of the second active material layer is selected from a spinel structure or olivine structure positive electrode material with high thermal stability but slightly low energy density. The present application provides a specific structure in which a lithium-rich lithium-supplementing layer is designed between a layered positive electrode material and a spinel structure or olivine structure positive electrode material. The lithium-rich lithium-supplementing layer plays a role in replenishing lithium during the first cycle of charge and discharge of the battery, thereby improving the first-effect coulomb efficiency of the battery; the layered positive electrode material is easier to deintercalate lithium, and the lithium-rich lithium-supplementing layer close to the layered positive electrode material can more efficiently deintercalate and replenish lithium. Compared with the outer layer, the lithium-supplementing layer can shorten the lithium replenishment path, and it is easier to achieve deep lithium replenishment, avoiding uneven deposition of lithium in the outer layer. In addition, the structure of the positive electrode material with a spinel structure or an olivine structure is more stable, which can appropriately block the lithium loss of lithium supplementation, reduce the lithium dissolution of the positive electrode material, and slow down the formation of lithium dendrites. At the same time, the second active material layer can block and absorb the heat of the first active material layer to improve the safety of the battery. The outer solid electrolyte layer helps to regulate the uniform diffusion of lithium ions, and can play a role in physical isolation, improve the interface stability of the second active material layer during the first cycle, reduce the growth of interface impedance, and further improve safety performance. Therefore, the present application improves the safety of the battery while improving the energy density of the positive electrode material through the sequential design of the positive electrode plate structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is an exemplary structure of the high-safety and high-energy-density positive electrode plate structure of the utility model. DETAILED DESCRIPTION

[0021] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0022] In the description of this application, the term "multiple" refers to more than two (including two), similarly, "multiple groups" refers to more than two groups (including two groups), and "at least one" refers to more than one (including one, two, three, etc.).

[0023] The utility model provides a high-safety and high-energy-density positive electrode plate structure, which includes a carbon base coating, a first active material layer, a lithium-rich lithium-supplementing layer, a second active material layer, and a solid electrolyte layer in sequence from at least one side of a current collector to the outside.

[0024] In some embodiments, the current collector is selected from one of an aluminum foil current collector, a titanium foil current collector, and a silver foil current collector.

[0025] In some embodiments, the carbon base coating material is selected from one of graphene, nano carbon black, acetylene black, graphite, carbon nanotubes, and carbon nanowires. The aluminum foil current collector with the carbon base coating can also be directly purchased as an integrated product.

[0026] In some embodiments, the carbon primer layer has a thickness of 0.1-1 μm. Preferably, the carbon primer layer of the present application has a thickness of 500-600 nm.

[0027] The carbon bottom coating on the surface of the current collector can increase the contact between the positive electrode active material and the current collector to reduce the contact resistance and enhance the layer bonding strength. At the same time, it can reduce the corrosion problem of the electrolyte on the current collector and improve the battery stability.

[0028] In some embodiments, the first active material layer is selected from a layered structure positive electrode material, and the second active layer material can be selected from a spinel structure positive electrode material or an olivine structure positive electrode material.

[0029] In some embodiments, the layered positive electrode material is selected from at least one of NCM811, NCM622, NCM523, lithium cobalt oxide, and lithium nickel oxide. Preferably, the layered positive electrode material is selected from one of NCM811, NCM622, and NCM523.

[0030] In some embodiments, the spinel structure positive electrode material is selected from lithium manganese oxide, and the olivine structure positive electrode material is selected from at least one of lithium iron phosphate and lithium iron manganese phosphate.

[0031] In some embodiments, the lithium-rich lithium-supplementing layer material is selected from one of lithium salts or metallic lithium. The lithium salt is selected from one of lithium manganate, lithium nickelate, lithium vanadate, lithium titanate, and lithium oxalate. Preferably, the lithium-rich lithium-supplementing layer material of the present application is selected from lithium oxalate.

[0032] In some embodiments, the thickness of the first active material layer is 100-600 μm. Preferably, the thickness of the first active material layer of the present application is 100-300 nm. The thickness of the second active material layer is 50-300 μm. Preferably, the thickness of the second active material layer of the present application is 70-100 μm. The reasonable thickness combination of the second active material layer and the first active material layer is conducive to further improving the energy density of the system.

[0033] In some embodiments, the thickness of the lithium-rich replenishing layer is 1-50 μm. Preferably, the thickness of the lithium-rich replenishing layer of the present application is 5-10 μm. When the thickness of the lithium-rich replenishing layer can meet the lithium replenishment requirements, it is designed to be as thin as possible. The reasonable thickness design of the lithium-rich replenishing layer can better improve the first-effect coulombic efficiency of the positive electrode active material, which can generally reach more than 90%.

[0034] The material of the first active material layer is selected from a layered positive electrode material with high energy density but slightly lower thermal stability, and the material of the second active material layer is selected from a spinel structure or olivine structure positive electrode material with high thermal stability but slightly lower energy density. The present application provides a specific structure in which a lithium-rich lithium-supplementing layer is designed between a layered positive electrode material and a spinel structure or olivine structure positive electrode material. The second active material layer can block and absorb the heat generated by the first active material layer positive electrode material during the charging and discharging process, and can be used in conjunction with a silicon-based negative electrode system to improve the safety performance of the battery. The lithium-rich lithium-supplementing layer plays a role in replenishing lithium during the first cycle of charging and discharging of the battery, thereby improving the first-effect coulomb efficiency of the battery; the layered positive electrode material is easier to deintercalate lithium, and the lithium-rich lithium-supplementing layer close to the layered positive electrode material can more efficiently deintercalate and replenish lithium. Compared with the outer layer, the lithium-supplementing layer can shorten the lithium replenishment path, and it is easier to achieve deep lithium replenishment, thereby avoiding uneven deposition of lithium in the outer layer. In addition, the structure of the positive electrode material with spinel structure or olivine structure is more stable, which can properly block the loss of lithium during lithium supplementation, reduce the lithium dissolution of the positive electrode material, and slow down the formation of lithium dendrites. The lithium-rich lithium supplementation layer can also effectively fill the gap between the first active material layer and the second active material layer, reducing the risks caused by the particle size, tap density, and surface morphology of the two positive electrode materials during the electrode processing.

[0035] In some embodiments, the solid electrolyte layer material can be selected from one of a polymer electrolyte, an oxide electrolyte, and a sulfide electrolyte. The polymer electrolyte can be selected from at least one of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), and polyvinylidene fluoride (PVDF). The oxide electrolyte can be selected from at least one of lithium phosphorus oxynitride (LiPON), lithium aluminum titanium phosphate (LATP), lithium lanthanum titanium oxide (LLTO), and lithium lanthanum zirconium oxide (LLZO). The sulfide electrolyte can be selected from lithium thiophosphate (Li3PS4), high purity germanium sulfide germanium disulfide (Li 10 GeP2S 12 ), lithium thiophosphate (Li7P3S 11 Preferably, the solid electrolyte of the present application is selected from polymer electrolytes.

[0036] In some embodiments, the porosity of the first active material layer is 35-50%; the porosity of the second active material layer is 35-50%. The porosity of the solid electrolyte layer is ≥50%, and the thickness is 0.5-10μm. When the porosity of the solid electrolyte layer is ≥50%, it can not only improve the lithium ion conductivity of the positive electrode sheet and the interface stability of the first cycle battery, but also serve as a barrier layer to reduce the safety risks caused by lithium precipitation; in addition, the thickness of the solid electrolyte layer is set to 0.5-10μm. The relatively thin thickness can play the above role while having almost no effect on the mass energy density of the battery cell.

[0037] The outer solid electrolyte layer helps to regulate the uniform diffusion of lithium ions, and can also improve the interfacial stability of the second active material layer during the first cycle, reduce the growth of interfacial impedance, and increase battery life. At the same time, it can reduce or avoid the use of liquid electrolytes and further improve safety performance.

[0038] Each layer of the present application is prepared with a main material that plays a major role in each layer. In the actual preparation process, it is often necessary to add some other necessary ingredients for the purpose of layer preparation, such as adhesives, etc., and some other additives, such as conductive agents, etc., may also be added as needed. In order to better play the functional role of each layer, the mass content of the main material is preferably not less than 80%.

[0039] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below, but the scope of the present invention is not limited thereby.

[0040] An exemplary structure of the high-safety and high-energy-density positive electrode plate structure provided by the utility model can be as follows Figure 1 As shown, from both sides of the current collector 1 to the outside, the layers include a carbon base coating 2, a first active material layer 3, a lithium-rich lithium-supplementing layer 4, a second active material layer 5 and a solid electrolyte layer 6 in sequence.

[0041] Example 1

[0042] An exemplary structure of the high energy density and high safety positive electrode plate structure provided by the utility model can be as follows Figure 1 As shown, from both sides of the current collector 1 to the outside, the layers include a carbon base coating 2, a first active material layer 3, a lithium-rich lithium-supplementing layer 4, a second active material layer 5 and a solid electrolyte layer 6 in sequence.

[0043] As a specific embodiment, the carbon-coated aluminum foil can use a customized specification substrate, and the carbon base coating uses carbon nanotubes with a thickness of 500nm. The first active material layer is prepared as follows: 96% NCM811, 1% conductive carbon black, 1% carbon nanotubes CNT, and 2% polyvinylidene fluoride PVDF are mixed in proportion to prepare a slurry with a viscosity of 5500±500; the first active material layer slurry is coated on the carbon-coated aluminum foil current collector, and the double-sided surface density of the current collector is controlled at 550g / m 2 , roll the coated electrode and control the compaction density at 3g / cm 3 , the coating thickness is controlled at 183μm, and the pole piece A is obtained. Prepare the lithium supplement layer slurry, apply lithium oxalate, binder PVDF and conductive carbon black on pole piece A in a mass ratio of 96:2:2, and the coating thickness is 5μm. After drying, pole piece B is obtained. For the second active material layer coating, 96% lithium iron phosphate, 0.5% conductive carbon black, 1% carbon nanotubes CNT, 1.5% polyvinylidene fluoride PVDF and 1% polyvinyl pyrrolidone PVP are mixed evenly to prepare a slurry with a viscosity of 6000±1000; apply the above second active material layer slurry on pole piece B, and the double-sided surface density of the second active material layer is controlled at 200g / m 2 , roll the coated electrode and control the compaction density at 2.77g / cm 3 , the coating thickness is controlled at 72μm, and the pole piece C is obtained. The preparation of the above-mentioned pole pieces A, B, and C needs to be carried out at a dew point below -40°C. After drying, a solid electrolyte layer is applied, using polyacrylonitrile, and the thickness is controlled at 2μm to obtain pole piece D. The prepared positive pole piece is cut and die-cut, and the whole battery is assembled with the matched negative electrode and separator. The electrolyte is injected, and a practical high-energy density and high-safety battery cell is obtained after the formation and aging processes.

[0044] Example 2

[0045] As a specific embodiment, the difference between it and embodiment 1 is that the first active material layer is a lithium cobalt oxide LCO positive electrode material.

[0046] Example 3

[0047] As a specific embodiment, the difference between it and embodiment 1 is that the lithium-rich lithium-supplementing layer is lithium nickelate.

[0048] Example 4

[0049] As a specific embodiment, the difference from Embodiment 1 is that a lithium supplement slurry is prepared, and lithium oxalate, a binder PVDF, and conductive carbon black are coated on the electrode A in a mass ratio of 96:2:2, and the coating thickness is 2 μm.

[0050] Example 5

[0051] As a specific embodiment, the difference between it and embodiment 1 is that the first active material layer is prepared as follows: 96% NCM811, 1% conductive carbon black, 1% carbon nanotube CNT, and 2% polyvinylidene fluoride PVDF are mixed uniformly according to the proportion to prepare a slurry with a viscosity of 5500±500; the first active material slurry is coated on the carbon-coated aluminum foil current collector, and the double-sided surface density of the current collector is controlled at 600g / m 2 , roll the coated electrode and control the compaction density at 3g / cm 3 , the coating thickness is controlled at 200μm.

[0052] Example 6

[0053] As a specific embodiment, the difference between it and embodiment 1 is that, for coating the second positive electrode active material layer, 96% lithium iron phosphate, 0.5% conductive carbon black, 1% carbon nanotubes CNT, 1.5% polyvinylidene fluoride PVDF and 1% polyvinyl pyrrolidone PVP are uniformly mixed to prepare a slurry with a viscosity of 6000±500; the second active material slurry is coated on the pole piece B, and the double-sided surface density of the second active material layer is controlled at 250g / m 2 , roll the coated electrode and control the compaction density at 2.78g / cm 3 The coating thickness is controlled at 90 μm to obtain pole piece C.

[0054] Comparative Example 1

[0055] As a specific comparative example, the difference between it and Example 1 is that the carbon-coated aluminum foil can use a customized specification substrate, and the carbon bottom coating uses carbon nanotubes with a thickness of 500nm. The first active material layer is prepared as follows: 96% NCM811, 1% conductive carbon black, 1% carbon nanotubes CNT, and 2% polyvinylidene fluoride PVDF are mixed uniformly according to the proportion to prepare a slurry with a viscosity of 5500±500; the first active material slurry is coated on the carbon-coated aluminum foil current collector, and the double-sided surface density of the current collector is controlled at 550g / m 2 The coated electrode is rolled to obtain electrode A, and the compaction density is controlled at 3g / cm 3, the coating thickness is controlled at 183μm. The second positive electrode active material layer is coated by uniformly mixing 96% lithium iron phosphate, 0.5% conductive carbon black, 1% carbon nanotubes CNT, 1.5% polyvinylidene fluoride PVDF and 1% polyvinyl pyrrolidone PVP to prepare a slurry with a viscosity of 6000±500; the second active material slurry is coated on the pole piece A, and the double-sided surface density of the second active material layer is controlled at 200g / m 2 , roll the coated electrode and control the compaction density at 2.77g / cm 3 , the coating thickness is controlled at 72μm, and the pole piece B is obtained. The above-mentioned A and B pole pieces need to be prepared at a dew point below -40°C. After drying, a solid electrolyte layer is applied, using polyacrylonitrile, and the thickness is controlled at 2μm, and the pole piece C is obtained.

[0056] Comparative Example 2

[0057] As a specific comparative example, the difference between it and Example 1 is that the first active material layer is prepared as follows: 96% lithium iron phosphate LFP, 0.5% conductive carbon black SP, 1% carbon nanotube CNT, 1.5% polyvinylidene fluoride PVDF and 1% polyvinyl pyrrolidone PVP are mixed uniformly according to the proportion to prepare a slurry with a viscosity of 6000±500; the first active material slurry is coated on the carbon-coated aluminum foil current collector, and the double-sided surface density of the current collector is controlled at 200g / m 2 , roll the coated electrode and control the compaction density at 2.77g / cm 3 , the coating thickness is controlled at 72μm, and the pole piece A is obtained. Prepare lithium supplement slurry, apply lithium oxalate, binder PVDF and conductive carbon black on pole piece A in a mass ratio of 96:2:2, and the coating thickness is 5μm. After drying, pole piece B is obtained. Apply the second positive electrode active material layer, mix 96% NCM811, 1% conductive carbon black, 1% carbon nanotube CNT, and 2% polyvinylidene fluoride PVDF in proportion to prepare a slurry with a viscosity of 5500±500; apply the above second active material slurry on pole piece B, and the double-sided surface density of the second active material layer is controlled at 550g / m 2 , roll the coated electrode and control the compaction density at 3g / cm 3 , the coating thickness is controlled at 183μm, and the pole piece C is obtained. The preparation of the above pole pieces A, B, and C needs to be carried out at a dew point below -40°C. After drying, a solid electrolyte layer is applied, using polyacrylonitrile, and the thickness is controlled at 2μm, and the pole piece D is obtained.

[0058] Comparative Example 3

[0059] As a specific comparative example, the difference between it and Example 1 is that the carbon-coated aluminum foil can use a customized specification substrate, and the carbon bottom coating uses carbon nanotubes with a thickness of 500nm. The first active material layer is prepared as follows: 96% NCM811, 1% conductive carbon black, 1% carbon nanotubes CNT, and 2% polyvinylidene fluoride PVDF are mixed uniformly according to the proportion to prepare a slurry with a viscosity of 5500±500; the first active material slurry is coated on the carbon-coated aluminum foil current collector, and the double-sided surface density of the current collector is controlled at 550g / m 2 , roll the coated electrode and control the compaction density at 3g / cm 3 , the coating thickness is controlled at 183μm, and the pole piece A is obtained. The second positive electrode active material layer is coated, 96% lithium iron phosphate, 0.5% conductive carbon black, 1% carbon nanotubes CNT, 1.5% polyvinylidene fluoride PVDF and 1% polyvinyl pyrrolidone PVP are mixed evenly to prepare a slurry with a viscosity of 6000±500; the second active material slurry is coated on the pole piece A, and the double-sided surface density of the second active material layer is controlled at 200g / m 2 , roll the coated electrode and control the compaction density at 2.77g / cm 3 , the coating thickness is controlled at 72μm, and the pole piece B is obtained. Prepare lithium supplement slurry, apply lithium oxalate, binder PVDF, and conductive carbon black on pole piece B in a mass ratio of 96:2:2, and the coating thickness is 5μm. After drying, pole piece C is obtained. The preparation of the above pole pieces A, B, and C needs to be carried out at a dew point below -40℃. Apply a solid electrolyte layer on pole piece C, using polyacrylonitrile, and the thickness is controlled at 2μm to obtain pole piece D.

[0060] Battery preparation: The positive electrode sheets prepared in the above embodiments and comparative examples were rolled to the described thickness, cut and die-cut into length*width=28mm*42mm, and dried to a moisture content of less than 100ppm; the graphite negative electrode materials were mixed, slurried, coated and rolled, and the negative electrode sheet surface density was 225g / m 2 , compacted density is 1.6g / cm 3 , after cutting, die-cut into length*width=30mm*44mm, and dried to a moisture content of less than 200ppm; the designed N / P is 1.05; an automatic laminating machine is used to stack the positive electrode sheets, diaphragms, and negative electrode sheets in turn, hot-press and flatten them, and weld the tabs to obtain 5 positive electrode + 6 negative electrode dry cells, which are dried to a moisture content of less than 100ppm; after being placed in an aluminum-plastic shell, the battery is injected with liquid, sealed, and aged in an argon glove box to obtain a battery.

[0061] The 5V6A electrochemical test channel was used to test the initial coulombic efficiency, capacity, energy density, and cycle performance of the above-mentioned battery cells. The test method is as follows:

[0062] (1) First, the battery’s initial coulombic efficiency and energy density are calculated by charging and discharging at a constant current of 0.1C / 0.1C for one cycle.

[0063] (2) Then, the battery was charged and discharged for 200 cycles at a constant current of 0.5C / 0.5C to obtain the capacity retention rate of the battery.

[0064] The test results are shown in Table 1.

[0065] Table 1

[0066]

[0067] From the data results in Table 1, it can be seen that the first-effect coulombic efficiency and cycle stability of the batteries of Examples 1-6 using the high-safety and high-energy-density positive electrode plate structure of the present invention are significantly better than those of Comparative Examples 1-3.

[0068] Adding a lithium-rich lithium-supplementing layer between two active material layers can significantly improve the battery's cycle capacity retention rate. The test results of Examples 1-6 and Comparative Example 1 can verify that adding a lithium-rich lithium-supplementing layer plays a role in replenishing lithium during the first cycle of charge and discharge of the battery, which can improve the battery's first-effect coulomb efficiency, and the lithium-rich lithium-supplementing layer can also effectively fill the gap between the first active material layer and the second active material layer, reducing the risks caused by the particle size, tap density, and surface morphology of the two positive electrode materials during the electrode sheet processing, and improving the cycle stability of the positive electrode material.

[0069] Placing the spinel structure or olivine structure positive electrode material outside the layered structure positive electrode material can better improve the first-effect coulomb cycle stability of the battery. The test results of Examples 1-6 and Comparative Example 2 can verify that the spinel structure or olivine structure positive electrode material can block and absorb the heat generated by the layered structure positive electrode material during the charging and discharging process, and can appropriately block the lithium loss of lithium replenishment, reduce the lithium dissolution of the positive electrode material, and slow down the formation of lithium dendrites, thereby improving the cycle stability and safety of the battery.

[0070] Placing the lithium-rich lithium-replenishing layer in the middle of the two active material layers rather than on the outside can significantly improve the first-effect coulombic efficiency and cycle capacity retention rate of the battery. The test results of Examples 1-6 and Comparative Example 3 can verify that placing the lithium-rich lithium-replenishing layer close to the layered positive electrode material can more efficiently deintercalate and replenish lithium. Relative to the outer layer design, the lithium-replenishing layer can shorten the lithium-replenishing path and more easily achieve deep lithium-replenishing, avoiding uneven deposition of lithium in the outer layer; at the same time, the lithium-rich lithium-replenishing layer can also effectively fill the gap between the two active material layers, further improving the cycle stability of the battery.

[0071] The first-effect coulomb efficiency of Examples 1-2 proves that the utility model has a good lithium replenishing effect on the first active material layer of different materials, but the cycle capacity retention rate of the battery cell in Example 2 is lower than that in Example 1. This is because the cycle performance of the lithium cobalt oxide positive electrode material is lower than that of the ternary positive electrode material. Therefore, the cycle capacity retention rate of the battery in Example 2 is lower than that in Example 1.

[0072] The lithium-rich replenishing layer plays a role in replenishing lithium during the first cycle of charge and discharge of the battery, and effectively fills the gap between the two active material layers, further improving the cycle stability of the battery. Different lithium-rich replenishing layer materials have different effects on improving the first effective coulomb efficiency of the battery. From the test results of Example 1 and Example 3, it can be verified that the lithium-rich replenishing layer of lithium oxalate is better than the lithium-rich replenishing layer of lithium nickelate, because Ni 2+ and Li + When the radius is similar and the lithium-rich lithium-supplementing layer of lithium nickelate is located between the two active material layers, Li + Location is Ni 2+ Occupy, resulting in a part of Li + It cannot be embedded, so using lithium oxalate as the lithium-rich lithium-supplementing layer material can better improve the battery's first-effect coulombic efficiency and cycle stability.

[0073] If the lithium-rich lithium-replenishing layer is too thin or too thick, it will affect the final first-effect coulombic efficiency and cycle stability of the battery. From the data results of Example 1 and Example 4, it can be verified that: under the condition of meeting the lithium replenishment demand, the thickness of the lithium-rich lithium-replenishing layer is set as thin as possible, so that the lithium-rich lithium-replenishing layer can not only supplement the irreversible lithium loss of the first active material layer and the second active material layer during the first charge and discharge process, but also fill the gap between the two active material layers of different particle sizes and morphologies, and ensure the structural stability between the two positive electrode materials. However, when the thickness of the lithium-rich lithium-replenishing layer is too thin, there is an uneven distribution of the lithium-replenishing layer and insufficient lithium replenishment, resulting in poor lithium replenishment effect. Therefore, the thickness of the lithium-rich lithium-replenishing layer needs to comprehensively consider the balance between improving the battery cycle stability and the lithium replenishment effect.

[0074] The first active material layer material has high energy density but slightly lower thermal stability and first efficiency. The second active material layer material has high thermal stability and first efficiency but slightly lower energy density. If the ratio of the second active material layer thickness to the first active material layer thickness is too large or too small, it will affect the battery's first-efficiency coulombic efficiency, cycle performance and energy density. From the data results of Example 5 and Example 6, it can be verified that increasing the thickness of the first active material layer increases the battery energy density, but reduces the first efficiency and cycle performance; increasing the thickness of the second active material layer increases the cycle capacity retention rate and first efficiency, but the energy density is lower. In this case, a high-safety, high-gram capacity positive electrode plate is matched with a graphite negative electrode to prepare a battery cell. By adjusting the appropriate ratio of the second active material layer thickness to the first active material layer thickness to ≤0.5, the energy density of the battery cell can generally be above 140Wh / Kg, and at the same time, it can make up for the loss of cycle performance and first efficiency caused by increasing the energy density.

[0075] The above embodiments are only used to illustrate the technical solutions of the present application and are not used to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-safety and high-energy-density positive electrode sheet structure, which includes, from at least one side of the current collector to the outside, a carbon base coating, a first active material layer, a lithium-rich lithium-supplementing layer, a second active material layer, and a solid electrolyte layer.

2. The high-safety and high-energy-density positive electrode plate structure according to claim 1, characterized in that: The carbon bottom coating, the first active material layer, the lithium-rich lithium-supplementing layer, the second active material layer and the solid electrolyte layer are arranged in sequence on both sides of the current collector respectively.

3. The high-safety and high-energy-density positive electrode plate structure according to claim 1, characterized in that: The current collector is selected from one of an aluminum foil current collector, a titanium foil current collector, and a silver foil current collector.

4. The high-safety and high-energy-density positive electrode plate structure according to claim 1, characterized in that: The carbon base coating material is selected from one of graphene, nano carbon black, acetylene black, graphite, carbon nanotubes, and carbon nanowires; the carbon base coating has a thickness of 0.1-1 μm.

5. The high-safety and high-energy-density positive electrode plate structure according to claim 1, characterized in that: The material of the first active material layer is selected from layered positive electrode materials, and the material of the second active material layer is selected from spinel positive electrode materials or olivine positive electrode materials.

6. The high-safety and high-energy-density positive electrode plate structure according to claim 5, characterized in that: The layered structure positive electrode material is selected from one of NCM811, NCM622, NCM523, lithium cobalt oxide, and lithium nickel oxide; the spinel structure positive electrode material is selected from lithium manganese oxide; the olivine structure positive electrode material is selected from one of lithium iron phosphate and lithium iron manganese phosphate.

7. The high-safety and high-energy-density positive electrode plate structure according to claim 1, characterized in that: The lithium-rich lithium-supplementing layer material is selected from one of lithium salts or metallic lithium; the lithium salt is selected from one of lithium manganate, lithium nickelate, lithium vanadate, lithium titanate, and lithium oxalate.

8. The high-safety and high-energy-density positive electrode plate structure according to claim 1, characterized in that: The thickness of the first active material layer is 100-600 μm; the thickness of the second active material layer is 50-300 μm; the ratio of the thickness of the second active material layer to the thickness of the first active material layer is ≤0.5; the thickness of the lithium-rich lithium-supplementing layer is 1-50 μm.

9. The high-safety and high-energy-density positive electrode plate structure according to claim 1, characterized in that: The porosity of the first active material layer is 35-50%; the porosity of the second active material layer is 35-50%; the porosity of the solid electrolyte layer is ≥50% and the thickness is 0.5-10 μm.

10. The high-safety and high-energy-density positive electrode plate structure according to claim 1, characterized in that: The solid electrolyte layer material is selected from one of a polymer electrolyte, an oxide electrolyte or a sulfide electrolyte; wherein the polymer electrolyte is selected from one of polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, and polyvinylidene fluoride; the oxide electrolyte is selected from one of lithium phosphorus oxynitride, lithium titanium aluminum phosphate, lithium lanthanum titanium oxide, and lithium lanthanum zirconium oxide; the sulfide electrolyte is selected from one of lithium thiophosphate, high-purity germanium sulfide germanium disulfide, and lithium thiophosphate.

11. The high-safety and high-energy-density positive electrode plate structure according to claim 1, characterized in that: The thickness of the lithium-rich lithium-supplementing layer is 5-10 μm.